«I am convinced that we will not get into the Civil War...». Boris Yeltsin’s meeting with deputies of the Leningrad City Council, March 22, 1991 - A. D. Matlin; A. S. Puchenkov (Омский научный вестник: Серия "Общество. История. Современность", 2021)
The publication is dedicated to staying Boris Yeltsin in Leningrad, March 22, 1991, and his meeting with the deputies of the Leningrad City Council XXI convocation. A transcript of Boris Yeltsin’s speech to the Leningrad parliamentarians in the Mariinsky Palace is being introduced into scientific circulation. The publication of the document was carried out according to the modern rules of archeography. The authors of most of the questions asked to Yeltsin have been identified, and reference information on their persons has been provided. The content of the meeting in the Leningrad City Council reflects the severity of the internal political crisis in the USSR on the eve of its collapse, when the rivalry between the main political leaders of the country: the President of the USSR M. S. Gorbachev and the Chairman of the Supreme Soviet of the RSFSR B. N. Yeltsin became especially acute. The materials of the publication are of interest to specialists in the socio-political history of Russia at the end of the twentieth century.